DESAIN DAN UJICOBA MEDIA PEMBELAJARAN BERBASIS E-MAGAZINE DENGAN PENDEKATAN DILEMMAS STORIES SEBAGAI SUMBER BELAJAR PADA MATERI LARUTAN ELEKTROLIT DAN NONELEKTROLIT - Siska Juliani; Fitri Refelita (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2022)
This research was instigated by the development of science and technology encouraging efforts to make reforms in the use of technology results in the learning process. Thus, a design and test were designed for e-magazine teaching material with Dilemmas Stories approach in this research on Electrolyte and non-Electrolyte Solution lesson. It was Research and Development (R&D) with Borg and Gall procedure design, and it was administered at Senior High School of Plus Bina Bangsa Pekanbaru. The subjects of this research were the experts of media and material, the practicality test experts that were teachers, and students of Senior High School of Plus Bina Bangsa Pekanbaru. The object was e-magazine learning media with Dilemmas Stories approach as a learning source on Electrolyte and non-Electrolyte Solution lesson. The data collected in this research were in the forms of validation questionnaire and response questionnaire. The data obtained then were analyzed by using qualitative and quantitative descriptive analysis techniques. E-magazine developed was tested very valid with the percentage 86.25% by the experts of media and material, the practicality assessment was 93.26% by Chemistry subject teacher, and students gave good responses with the percentage 70%. Based on these results, it could be concluded that e-magazine with Dilemmas Stories approach as a learning source on Electrolyte and non- Electrolyte Solution lesson was valid and good.